Applying waste treatment scenarios in Toluca region (Mexico). - Nina Tsydenova (Diponegoro University, 2017)
Governments in emerging countries need to analyse waste treatment alternatives, other than landfills, in order to decrease environmental pollution and socio-economic impacts. This study is assessing several alternative scenarios of waste treatment in Toluca municipality (Mexico) such as sanitary landfill, combustion of landfill gas, waste incineration (WtE), mechanical-biological treatment (MBT) and combination of anaerobic digestion (AD) and sanitary landfill under the condition of source waste separation. The objective of the research is the identification of the most feasible waste treatment scenario for developing countries which have the high percentage of organics on waste stream. The assessment is implemented from several perspectives: greenhouse gas (GHG) emissions, economic feasibility and consideration of informal recycling sector. The emissions generated at the baseline scenario are high due to the great percentage of organics in the municipal solid waste (MSW). The WTE and MBT facilities generate the lowest emissions but have a high gate fee. The scenario involving AD and sanitary landfill has the lowest gate fee while its emissions are significantly reduced compared to the baseline. The author believes that widespread adoption of AD systems, together with the source separation scheme, can be the starting point in the implementation of sustainable waste management in transition countries, such as Mexico.